An empirical analysis of the profitability of Chinese Banks - Wang, Shaowen (2018)
Abstract Employing the Stochastic Frontier Approach (SFA) and the System Generalised Method of Moment (SGMM), this paper aims to estimate the determinants of dynamic profitability of 210 Chinese commercial banks in the time period from 2013 to 2017. Among the two estimation techniques in this paper, SFA model is applied to obtain the cost efficiency scores of the sample banks which are used in the subsequent study, and the SGMM model is mainly discussed in this the performance study. Indicators at micro, meso and macro levels are selected according to provisions literature and the Return on Average Assets (ROAA) of a bank is used as the measurement of banks profitability. The results show that multiple determinants are influencing banks profitability at the same time. The ratio of Loan to Total Assets, Equity to Total Assets, GDP Growth Rate and Inflation Rate are found to have significant positive relationship with ROAA, while the ratio of Loan Loss Provisions to Total Assets, Loan Reserves to Gross Loans, The ratio of Net Loans to Deposits plus Short-Term Funding and the cost-to-Income ratio and are found to have negative relationship with ROAA. However, several indicators as Bank Size, Z-Score, Unemployed Rate and Cost Efficiency score are shown to have insignificant influence on a bank’s profitability in this case.